2020
DOI: 10.1590/s1678-9946202062016
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection in the genital tract of non-pregnant females: a systematic review

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…It is well documented that ZIKV can be sexually transmitted between humans [7][8][9][10][11][12][13][14]. The first evidence of sexual transmission was provided in a case report that describes a woman in the United States in 2008 with no recent travel history who developed a symptomatic ZIKV infection after sexual intercourse with her husband, a convalescent ZIKV patient who had recently returned from Senegal [4].…”
Section: Zika Virus: Sexual Transmission Between Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that ZIKV can be sexually transmitted between humans [7][8][9][10][11][12][13][14]. The first evidence of sexual transmission was provided in a case report that describes a woman in the United States in 2008 with no recent travel history who developed a symptomatic ZIKV infection after sexual intercourse with her husband, a convalescent ZIKV patient who had recently returned from Senegal [4].…”
Section: Zika Virus: Sexual Transmission Between Humansmentioning
confidence: 99%
“…Many review articles have been written on the subject. Most of these articles have focused exclusively on ZIKV, but a few encompass the entire family Flaviviridae and, occasionally, arboviruses from the order Bunyavirales and family Togaviridae [ 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Here, we provide a review on the urogenital localization of arboviruses and their potential to be sexually transmitted between vertebrates and include, for the first time, every taxonomic group that contains arboviruses ( Table 1 and Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…No caso da infecção Zika, além da picada do mosquito da espécie Aedes aegypti, a via sexual também é outra forma de transmissão 4 . A transmissão sexual se explica, dentre outros fatores, pela possibilidade de persistência do vírus no trato genital feminino 5 Quanto às características clínicas, quando é sintomática, ocorre febre baixa, exantema maculopapular, artralgia, mialgia, cefaleia, hiperemia conjuntival e, menos frequentemente, edema, odinofagia, tosse seca e alterações gastrointestinais, principalmente vômitos. 6 Segundo Aguiar, Araújo, 2016 7 , em 2015, o Ministério da Saúde (MS) anunciou a presença do vírus da Zika no líquido amniótico de duas gestantes da Paraíba cujos fetos passaram a apresentar pouco desenvolvimento do perímetro cefálico em momento coincidente ao relato de sintomas do vírus Zika na gestante.…”
Section: Introductionunclassified
“…Animal studies showed that ZIKV can infect a wide range of organs in a similar manner to that observed in humans. Some of these immune-privileged organs include the eyes [47,48], and the male [49] and female genital tracts [50,51]. Additionally, after the initial infection, the virus can persist for months and be found in different body fluids, such as ocular secretions, urine, and semen [52,53].…”
Section: Introductionmentioning
confidence: 99%